DANSON JOHI PADA LINGKUNGAN KERJA YANG TERGAMBAR DALAM MANGA MINNA NO DOUBUTSUEN KARYA AKIYO KUROSAWA - Anak Agung Bagus, Darmayuda (Humanis; Volume 14. No.1. Januari 2016, 2016)
The title of this thesis is “Danson Johi in Working Environment which described in Minna no Doubutsuen Manga written by Akiyo Kurosawa”. This research’s purpose is to find danson johi in working environment and its impact to the main character in Minna no Doubutsuen manga. The theory applied are socialist feminism literary theory proposed by Djajanegara (2003) and semiotic theory proposed by Danesi (2010). The method used to analyze the data in this study is the dialectical method. The results of this study show that danson johi experienced by Izumi in the work environment includes (1) stereotypes, (2) subordination, and (3) violence. Danson johi impact on Izumi character: (1) Izumi becomes emotional and (2) Izumi becomes uncomfortable on working.
Keywords: danson johi, feminism, working environment